Technology, Learning Communities and Young People: The Future Something Project. (20th March 2013) - Herne, Steve; Adams, Jeff; Atkinson, Dennis; Dash, Paul; Jessel, John
Abstract: The Future Something Project (FSP), a two‐year action research project, was devised to nurture the creative and technological talent of small groups of young people at risk by creating a structured network, mentored and driven by creative professionals exploring innovative ways for the two distinct target groups to work together. The project practice is located within the new field of interaction design and takes a social and critical approach to art and design pedagogy. The external research team found that one valuable way of looking at the FSP enterprise was through the social theory of communities of practice (CoPs) developed in the 1990s by Lave and Wenger. The creation of a learning community as a pedagogical strategy is central to the conception and practice of this project. This article, therefore, sets out to apply an existing theory to a new art and design context together with more general thoughts on learning communities. It explores the potential of new technologies and different settings to effect learning within structured networks and local and virtual communities of practice.